2002
DOI: 10.1161/01.cir.0000019743.11941.3b
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Angiographic Follow-Up After Coronary Stent Placement in Native Coronary Arteries

Abstract: Background — Although coronary stents have been proved effective in reducing clinical cardiac events for up to 3 to 5 years, longer term clinical and angiographic outcomes have not yet been fully clarified. Methods and Results — To evaluate longer term (7 to 11 years) outcome, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 22 publications
9
113
1
3
Order By: Relevance
“…16,17) This regression is accompanied mainly by a reduction in proteoglycan, with no change in smooth muscle cell density or collagen content.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) This regression is accompanied mainly by a reduction in proteoglycan, with no change in smooth muscle cell density or collagen content.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is a report of late in-stent luminal renarrowing which occurred more than 4 years after BMS deployment. 1) Hasegawa, et al demonstrated that 43% of new in-stent restenosis (ISR) lesions that develop beyond 5 years are clinically represented as ACS.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is merely a hypothesis because angiographic ISR with neointimal growth at the second study does not induce late complication. 9) Abnormal platelet aggregation also plays a role in stent thrombosis. The WRIST PLUS study 10) demonstrated the efficacy of prolonged intentional antiplatelet therapy against LST with prior brachytherapy.…”
Section: Discussionmentioning
confidence: 99%